Peranan Parasitoid Telur Penggerek Batang Padi Putih Scirpophaga innotata (Walker) Pada Berbagai Fase Pertumbuhan Tanaman Padi - Awaluddin, Awaluddin; Gassa, Ahdin; Agus, Nurariaty (Jurnal Penelitian Pertanian Tanaman Pangan, 2019)
White stem borer Scirpophaga innotata Walkers is known as a species that always causes loss of rice yields in Indonesia and the Asia region and Australia. White stem borer attacks all stages of rice plant growth starting in the nursery until harvest. Until now, synthetic chemical pesticides are still a mainstay of farmers in controlling these pests. Then it is necessary to promote biological pest management, the use of biological agents is pest management technology because a save, economical and effective. Biological control through multiplication and parasitoid release needs to be focused on parasitoid it has adapted to the local environment. This study aims to examine the role of egg parasitoid S. innotata through the type and level of egg parasitization at various phases of rice plant growth. This research was conducted by collecting as many white rice stem borer eggs as possible based on the growth phase of rice plants, i.e. age 11-25 days after planting (DAP), 26-40 DAP, 41-55 DAP, 56-70 DAP, and 71-85 DAP. Observations were made by counting hatching and non-hatching eggs, as well as the type and number of parasitoids that appeared. The results show that the egg parasitoid found was Trichogramma japonicum Ashmead, Tetrastichus schoenobii Ferriere, Telenomus rowani Gahan. The highest level of egg parasitization is at 71-85 DAP.